PROBLEMS IN THE OPERATION OF INFORMATION RESOURCE CENTERS AND THEIR CAUSES - Pirmedova Khayitgul Muxammedovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article provides a systematic analysis of the existing problems in the activities of information resource centers at higher education institutions in Uzbekistan and their underlying causes. In particular, infrastructure imbalances, financial constraints, insufficient staff qualifications, shortcomings in the management system, and inadequate integration of information systems have been identified as the main problems. Additionally, the obstacles in the digital transformation process and their impact on educational and scientific activities are highlighted. The author has developed scientifically grounded proposals and recommendations for developing information resource centers as strategic institutions, implementing a unified KPI system, and establishing a digital management model.